Microcredit and multidimensional poverty in Algeria: does gender matter? Case study: National Agency For Management Of Credit / Department of Boumerdes - Hadefi, Abdelkrim Zoheir; Bouchetara, Mehdi; Zerouti, Messaoud (Management and Entrepreneurship: Trends of Development, 2022)
This article attempts to assess the impact of microcredit on the economic well-being and implicitly the degree of multidimensional poverty of women in Algeria. Based on data from a survey of 228 microcredit recipients in the department of Boumerdes in Algeria. The study showed that participation in microfinance services provided by the national agency for management of microcredit (ANGEM ) could be a tool for women to acquire the capacity to make strategic choices concerning their lives. By having access to microfinance services, women can set up their own businesses and consequently improve their status within the household and in their communities. Only 26 women participated in the survey. Using the Mann Whitney U test, the results show a significant difference between the impacts generated by microcredit on both genders based on the asset ownership index where female beneficiaries feel more impacted than male members do. These results call for further questions. ANGEM is not Micro-Finance Institution (MFI) like the others. It is a public agency. JEL Classification D10, O30, M54, I32.